KAJIAN DAYA DUKUNG SUMBER AIR HUJAN TERHADAP RENCANA TATA RUANG WILAYAH (RTRW) KOTA DEPOK - JASURI SA’AT (Politeknik Negeri Jakarta, 2014)
ABSTRACT A city development is indicated by population growth and more complete facilities compare to rural area. Depok is one of city with massive development nowadays with high economic potential. In 2010, depok population is 1.675.213 peoples, this number has increase by 31.65% compare to 2000 (1.145.091 peoples), the average population growth is 3.64% per year. In line with high population growth and changing on people dynamic, most of green open space area (rth) has shifting the function into used spaced with many buildings is develop nowadays for residential (house, apartment), office building, restaurant, etc. For supporting population growth, one of the most important factor need to consider is the availability of reserved water for supporting people’s daily life. The main objective of this study was to determine the potential capacity of rain water sources to the spatial plan of depok city in 2010. Some of water source for covering all depok area are kali, situ & ground water. Currently, the usage of ground water is more dominant (used by 82.5% of total population). Based on the research result, potential source of rain water in depok is sufficient because the annual rainfall duration is very high (1106 – 4579 mm), resulting on the surplus value of dependable flow in each districts, except in beji district during dry season, in september and oktober. Keyword: rain water sources, rainfall, spatial plan.